TEACHING METHOD AND VOCABULARY MASTERY INFLUENCE TOWARD STUDENT’S SPEAKING SKILL - Ahmad Syafiq; Bambang Eko Siagiyanto (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2019)
The aim of this research is to know if there are effects of teaching method and vocabulary mastery on student’s speaking skill at private senior high schools in Teluk Betung, Bandar Lampung. The sample of this research is 60 students. This research is experimental research with two factors, teaching method using Communicative Language Teaching (CLT) and Conventional Method and Vocabulary Mastery. The data about vocabulary mastery and speaking skills are taken through tests which their validity and reliability have been tested. The researcher used SPSS Program 20 to analyze the data. The results are: experimental class (A1) has to mean score 68, it is more than a control class (A2) that has to mean score 59,97. Testing of three hypotheses used ANOVA (analysis on variants), it has got a sig. score 0,000 in communicative language teaching and vocabulary mastery got sig 0,002. It means the first hypothesis, there is a significant effect of CLT on students’ speaking skill is accepted. The second hypothesis, there is a significant effect of vocabulary mastery on students’ speaking skill is also accepted. While the third hypothesis, there are the effects of teaching method using CLT and vocabulary mastery on students’ speaking skill is rejected.